Evaluation of the Wira-Wiri Feeder Program Route FD8 (Osowilangun Terminal – UNESA) as Public Transportation in the City of Surabaya - Achmad Farhan Dwi Kusuma; Tauran T; Suci Megawati; M. Noer Falaq Al Amin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Public transportation has become a strategic necessity in the City of Surabaya due to the increasing number of private vehicles. In response, the city government launched the Wira-Wiri Feeder Program integrated with the Suroboyo Bus system. This study aims to evaluate the implementation of the program on Route FD8 (Osowilangun Terminal–UNESA) by applying Daniel Stufflebeam’s CIPP Evaluation Theory, which consists of Context, Input, Process, and Product. The research employs a qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that although the program is relevant to the need for improving accessibility, several issues remain in the input and process aspects, including the limited number of fleets (4 units), inadequate bus stop facilities, operational disruptions caused by traffic congestion and flooding, and service implementation that has not fully met the required standards. As a result, the program has only provided an affordable alternative mode of public transportation but has not significantly increased public interest in using Route FD8. The implications suggest the need for fleet renewal, improvement of bus stop facilities, strengthened operational supervision, and corridor mitigation strategies (traffic congestion and flooding) to ensure the service meets Minimum Service Standards and supports the shift from private vehicles to public transportation.